RESPON TANAMAN SAWI HIJAU (Brassica juncea L. ) TERHADAP PERLAKUAN PUPUK KASCING PADA TANAH LEMPUNG LIAT BERPASIR - I Putu Leo; Bagus Putu Udiyana; I Made Suryana (Agrofarm: Jurnal Agroteknologi, 2022)
Green mustard (Brassica juncea L) is one type of vegetable that is much loved by the community, because it tastes good, is easy to get, and is not too difficult to cultivate. The production of mustard greens in Indonesia from 2015 to 2018 continues to experience an increase in the production of mustard plants in line with the rate of population growth or can be said in line with efforts to improve community nutrition. The study, entiled “Growth and Yield Response of Green Mustard (Brassica juncea L) to Kascing Fertilizer Application” conducted at Tukad Oos Street, Renon, South Denpasar, Denpasar City, Bali. This study began in 23 October until 3 December 2019. This study aims to know the best dose of Kascing Fertilizer for green mustard growth and yield. This study using Cluster Random Sampling with 6 treatments which repeated 4 times so that it gets 24 treatments. The result of this study showed that in Kascing Fertilizer application with a dose of 15 tons ha-1 (K5) is able to give very good result to the fresh plant weight parameters about 271,89g and total oven dry weight of plants about 21,49g.